As built case studies for BIM as conflicts detection and documentation tool. Issue 1 (1st January 2017) - Abd, Abbas M.; Khamees, Alaa S.
Abstract: As built documentation provide critical information that is needed during and afterward the construction. This process serve as a foundation upon which all changes, modifications or otherwise, made during the construction so that it can quickly obtain information about any design change. After construction, it serve as ready information source about what was actually built. Conflicts of the design documents with as built is crucial aspect of construction projects in order to prevent excessive cost of delays and work correction during operation and maintenance or renovation phases. Traditional documentation method sometime fails to serve in managing the development, rehabilitation and renovation of existing buildings. The lack of appropriate documents, change orders and as built-drawing for existing buildings are very common. These obstacles can be solved by the collaboration of all stakeholders at different phases of the project life cycle to insert, extract, update or amend related information. Since Building Information Modelling (BIM) has the potential to create a single model that offers visualization, clash detection, construction phases, and materials and testing together, this research will utilize the ability of BIM through case studies to address the conflicts detection through the project life-cycle. The results illustrates the main conflicts that had detected between the existing buildings and the available construction documents. The results of the two case studies prove that BIM model was very correlated to as built in term of quantities take off (coefficient was 95.8 and 99.8%) and in the final shop drawing. Also, the root mean square error was very little for BIM model (RMSE was 7.17 and 6.65) compared with traditional process for the quantities estimation compared with traditional process (RMSE was 43.75 and 47.33). These indications refer to high accuracy of BIM as a powerful tool for the re-documentation of existing building and their conflicts detection.